The National Broadband Network: What Difference will it make to Broadband Availability in Australia? - Campbell, Leith H; Suessspeck, Sascha; Hinton, Kerry (Journal of Telecommunications and the Digital Economy, 2018)
We provide a bottom-up analysis of broadband availability in Australia without the NBN and with the NBN. For Australia without the NBN, we have assumed that broadband availability, in terms of access speed, would have continued to evolve; in particular, we have assumed that all DSL access would have been enhanced to ADSL2+. For Australia with the NBN, we concentrate on the Multi-Technology Mix version now being deployed in the fixed-line footprint. The NBN can make a difference both in terms of the geographical availability of broadband access and in the maximum access speeds provided. We consider both these aspects for the period after the current NBN has been fully deployed. Our analysis is based solely on publicly available information and census data from 2011. We find that the NBN will extend fixed-line broadband availability only marginally. In terms of access speed, we find that a further 17% of the population will have access to 10 Mb/s downstream and a further 65% of the population will have access to 25 Mb/s. Only a further 11% of the population will have access to 10 Mb/s and above upstream. The improvement in availability is particularly marked in outer suburban areas of the major cities and in regional centres.